PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI - Majidah, Yuniz; Rachmawati, Ike Kusdyah; Karnawati, Tin Agustina (LP2M Institut Teknologi dan Bisnis Asia Malang, 2020)
The principal should have caring to improving the quality of education. Such caring should be demonstrated with the will and ability to develop themselves optimally, so the teachers and education personnel can improve their performance. The teacher's performance is influenced by several factors are situational leadership style, work motivation and job satisfaction.The purpose of this research is to know and analyse the influence of situational leadership style, job motivation, and job satisfaction on the teacher's performance, the influence of situasional leadership style and job motivation to the performance of teachers moderated in job satisfaction. The population of this research is the teachers of accredited pre-primary school in Singaraja Cit Bali. The data collection techniques in this research are the observation and distribution of questionnaires. This research uses data analysis methods using SmartPLS software. The results showed that the situational leadership style, job motivation, and job satisfaction affects the teacher’s performance of the accredited pre-primary schools in Singaraja City Bali, and the situational leadership style, and job motivation have no effect the teacher’s performance who are moderated job satisfaction at the pre-primary school accredited in Singaraja City Bali.